Lactobacillus acidophilus alleviate Salmonella enterica Serovar Typhimurium-induced murine inflammatory/oxidative responses via the p62-Keap1-Nrf2 signaling pathway and cecal microbiota - Li, Haihua; Ma, Xinyi; Shang, Zhiyuan; Liu, Xuejiao; Qiao, Jiayun (Frontiers in Microbiology, 2025)
BackgroundSalmonella enterica Serovar Typhimurium (S. Typhimurium) infection can cause inflammation and oxidative stress in the body, leading to gastroenteritis, fever and other diseases in humans and animals. More and more studies have emphasized the broad prospects of probiotics in improving inflammation and oxidative stress, but the ability and mechanism of Lactobacillus acidophilus (LA) to alleviate the inflammatory/oxidative reaction caused by pathogens are still unclear.Methods and resultsIn this study, we treated the mice with LA for 14 days, infected them with S. Typhimurium for 24 h, and sacrificed the mice to collect samples. We found that the early intervention of LA alleviated the pathological injury and reversed the down-regulation of the duodenal and hepatic tight junction protein mRNA levels caused by S. Typhimurium infection. Compared with S. Typhimurium group, LA early intervention increased the expression of antioxidant enzymes, but decreased the levels of serum malondialdehyde (MDA), interleukin-8 and tumor necrosis factor-α (TNF-α). Additionally, LA early intervention significantly increased Nrf2 mRNA expression in the liver and decreased Keap1 mRNA expression in the duodenum compared to the S. Typhimurium group. Furthermore, early LA treatment reduced the abundance of Bacteroides acidificiens, increased the abundance of Akkermansia, and alleviated the decrease in SCFAs levels in the cecum of S. Typhimurium-infected mice. Spearman correlation analysis showed that there was a certain correlation between cecal flora and serum indicators and short chain fatty acids.ConclusionTaken together, the results indicate that LA early intervention may alleviates S. Typhimurium-induced inflammation and oxidative responses in mice by activating the p62-Keap1-Nrf2 signaling pathway and regulating the gut microbial community.Significance and impact of the studyExploring the ability of LA to resist animal oxidative stress and microflora regulation caused by pathogenic microbes, so as to provide more options for developing healthy disease-resistant feed additives.